The relation between oral candidiasis and the type of denture base material in animal model - Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban (IIUM Press, International Islamic University Malaysia, 2017)
The human oral cavity is a unique ecological niche because it is constantly bathed in saliva, a biological fluid with potent antifungal and antibacterial activity. In addition, the constant salivary flushing action mechanically inhibits the accumulation of microorganisms in various oral niches. Candida albicans is the micro-organism which have been known to have a well established pathogenic role in denture stomatitis .Acrylic dentures may be a source of reinfections in several cases of denture stomatitis, and may be responsible for relapse after cessation of antifungal treatment .Moreover, it was found by several investigators that Candida cells were present in larger number on denture smears than mucosal smears.Metal bases are more hygienic than acrylic bases, and the cure of what was thought to be allergy to acrylic by replacement with metal base was in fact brought about by eradication of reinfecting organisms found that inflammation was much more frequent under resin based dentures than metal based dentures.